FAKTOR PENYEBAB ANAK PUTUS SEKOLAH JENJANG PENDIDIKAN SEKOLAH DASAR - Yanti, Novi; Zakso, Amrazi; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â AbstractThis study aims to determine the causative factors and efforts to overcome dropouts from elementary school level in Nanga Raya Village, Belimbing Hulu District, Melawi Regency. The method used in this research is quantitative with descriptive methods. There are two data sources used, namely primary data sources and secondary data sources. Data collection techniques and tools used are in-depth interviews and documentation. The results of this study indicate there are two factors that cause children to drop out of school, namely: internal factors and external factors. Internal factors are factors originating from within the child such as the low ability of children to learn, feeling lazy in learning that causes students to stay in the classroom. after staying in class the student will drop out of school. Furthermore, external factors are factors that originate from outside the child itself such as the educational background of the parents, the economic ability of the family and the environment in which they live. Then the effort to overcome so that children do not drop out of school, that is, always provide support and motivation in each child's learning process. Furthermore, the government of Nanga Raya Village, Belimbing Hulu Subdistrict has also built a one-stop PAUD and junior high school educational institution. Then the village government also provides special assistance for underprivileged children.Â Keywords : Children, Causative Factors, Dropping Out of School